Recent Leaps Towards Free Trade - The Impact on Norwegian Industry and Trade Patterns - Taran Fæhn; Leo A. Grünfeld (Statistics Norway, Research Department, 1996)
In this study we model effects on Norwegian industry and trade patterns of the recently implemented trade reforms - the WTO-agreement, the EEA-treaty, the OECD ship building reform and the EFTA fishing agreement - through changes in tariffs, NTBs, government procurement and subsidy policy as well as shifts in foreign prices and demand. We employ a highly disaggregated CGE model to simulate the difference between an economy adapted to the mentioned reforms and an economy based on a multilateral maintenance of the pre-reform trade system. Exports and import shares are modelled differently depending on commodity characteristics. Labour supply and national wealth are exogenously determined in order to focus on the gains from reallocations of given resources. The results indicate strong effects on the patterns of industry and trade. Specifically, we observe an increase in the production of services and highly processed goods, and a decrease in the production of raw materials and less processed commodities.
Keywords: F14; F15; F17; 330; Trade reform; European economic integration; CGE analysis; Norway